Professional journalistic style. An attempt to define - Lilia R. Duskajewa (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
The article substantiates the distinction of professional journalistic language as a variant of langue representing journalistic style, and implemented in three groups of speech genres – informing, estimating and stimulating. Alongside stylistic features common with journalistic macrostyle, this professional language has its own specific characteristics, expressed through faithfulness to the facts, social estimation and administrative stimulation. Stylistic analysis of even only one genre – stimulating – reveals that the professional and linguistic activities of journalists can be analysed as typical execution algorithms, using the aforementioned method. The article demonstrates that the proposed analysis of speech representations in professional language can be productive for the study of language in action in the journalistic sphere of communication.